Analisis Pengaruh Harga, Kualitas Produk, Merek dan Promosi Terhadap Keputusan Pembelian Air Minum kemasan Merek Aqua (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis UMS) - Susanto, Herry; , Muzakar Isa, SE., M.Si (2016)
This study aimed to analyze: 1) the effect of price on purchase decisions aqua bottled water brands. 2) the impact of product quality on purchase decisions aqua bottled water brands. 3) brand influence on purchasing decisions aqua bottled water brands. 4) the effect of promotions on purchase decisions aqua bottled water brands. 5) the effect of price, product quality, brand and promotion together on purchasing decisions aqua bottled water brand. Populations that are objects of this study are students of the Faculty of Economics, University of Muhammadiyah Surakarta that use or have ever bought aqua. The samples used 100 respondents. The sampling technique used in this study is incidental sampling. The method used in this research is by using multiple linear regression analysis to test the hypothesis that the t test and F test Before using multiple linear regression analysis, performed classical assumption beforehand. Based on t test results showed that: 1) Prices positive and significant impact on consumer purchasing decisions. 2) Quality of products positive and significant impact on consumer purchasing decisions. 3) Brand positive and significant impact on consumer purchasing decisions. 4) The promotion of positive and significant impact on consumer purchasing decisions. While the results of the F test showed that price, product quality, brand and promotion simultaneously have influence on consumer purchasing decisions. Rated R Square of 0,501artinya that 50.1% change in consumer purchasing decisions can be explained by a change of independent variables (price, product quality, brand and promotion).